Gagasan Kebangsaan Mohammad Natsir dan Kontribusinya dalam Pemikiran Keislaman - jatim mistar (STIU Al-Mujtama Pamekasan, 2019)
Abstract: Indonesia is a state of law based on Pancasila. Natsir, views Pancasila as part of Islamic values, but that does not mean Pancasila is Islam. Islam is wider than the five precepts in the Pancasila. The five precepts only describe a portion of Islamic teachings, it can not represent the full teachings of Islam. For Natsir Pancasila to flourish in the fold of the Qur’an, the Pancasila can be realized or carried out well only in Islamic societies and countries. The State, for Natsir is the tool for Muslims to realize the Divine laws for the safety and tranquility of man. This is where Natsir sees the need for a driving force to realize Islamic laws, so Natsir emphasizes that Islam and the state are two unified relegio-political entities. The state for Natsir is not a goal, but a driving force for realizing Islamic laws, however, to realize those laws, an educated and high-minded society is always needed. For Natsir, a country will progress if its people are educated. According to him education is the most powerful role to advance a nation in lifting or increasing the condition of the people who are immersed in the mud of retardation. Keywords: State, Pancasila, Islam, education